2012
DOI: 10.1210/jc.2012-1951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on sRAGE Levels and Cardiometabolic Risk Factors in Patients with Type 2 Diabetes: A Randomized Controlled Trial

Abstract: Aerobic exercise increases sRAGE levels along with improvement of various cardiometabolic risk factors in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 32 publications
3
81
1
6
Order By: Relevance
“…nâmicas em mulheres na pós-menopausa acometidas por alterações metabólicas, vários são os estudos que encontraram efeito benéfico do exercício físico 17,18,[20][21][22] . Verificou-se que a redução dos valores antropométricos aconteceu tanto após a realização de exercícios de caminhada moderada por doze 21 ou dezesseis semanas 17 , como após a realização de programas com exercícios combinados (aeróbios e de força) durante longos 20 e curtos 21 períodos, corroborando com os achados deste estudo. Os exercícios físicos propostos no presente estudo foram suficientes para melhorar os valores da pressão arterial sistólica (PAS), sem alterar a diastólica.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…nâmicas em mulheres na pós-menopausa acometidas por alterações metabólicas, vários são os estudos que encontraram efeito benéfico do exercício físico 17,18,[20][21][22] . Verificou-se que a redução dos valores antropométricos aconteceu tanto após a realização de exercícios de caminhada moderada por doze 21 ou dezesseis semanas 17 , como após a realização de programas com exercícios combinados (aeróbios e de força) durante longos 20 e curtos 21 períodos, corroborando com os achados deste estudo. Os exercícios físicos propostos no presente estudo foram suficientes para melhorar os valores da pressão arterial sistólica (PAS), sem alterar a diastólica.…”
Section: Discussionunclassified
“…Em contrapartida, Bateman et al 18 verificaram reduções somente nos valores de pressão arterial diastólica (PAD) após 16 semanas de exercícios físicos aeróbios combinados ao de força; este fato pode estar relacionado à faixa etária dos participantes do estudo, que possuíam entre 18 e 70 anos. Entretanto, as mulheres participantes do estudo de Choi et al 21 apresentaram melhoras tanto na PAS quanto na PAD após 12 semanas de caminhada; este foi o único protocolo que ofertava atividade física cinco vezes por semana, sendo que a frequência semanal de exposição pode ter sido o diferencial para os resultados encontrados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The lower levels of sRAGE in the obese women might indicate that the intraovarian levels of AGEs exert an exaggerated effect at the level of the oocyte thus altering the molecular and energetic reserve that are needed to sustain normal meiosis in the oocyte [35]. Interestingly, caloric restriction induced weight loss increased serum sRAGE levels by approximately 150% [90] and sRAGE is expressed by inflammatory cells, such as monocytes and macrophages [91] and its production reduced systemic inflammation [92][93][94][95][96][97].…”
Section: Obesity Is An Inflammatory State Characterized By Alterationmentioning
confidence: 99%
“…Despite the fact that the exact mechanisms are still elusive, recently reported data suggest that AGE reduction could be involved in vascular protection exerted by exercise. In fact, it was recently demonstrated that aerobic exercise decreases plasma AGE-associated fl uorescence in obese Zucker rats [196] and increases sRAGE levels with improvement of vascular function in DM type 2 [197] and aged [198] patients. These fi ndings strongly suggest that exercise practice aff ects multiple mechanisms intracellularly that interfere in glycative and oxidative modifi cations of proteins.…”
Section: Exercisementioning
confidence: 99%